Z-67 / 8-coated C / N catalyst for advanced oxidation of persulfate as well as preparation method and application of Z-67 / 8-coated C / N catalyst

By encapsulating ZIF-67 in ZIF-8 material to form the Z-67/8@C/N catalyst, the problem of Co2+ easily causing secondary pollution in the homogeneous catalytic system is solved, and efficient ROS generation and pollutant removal are achieved It degrades without causing secondary pollution and is in line with the principle of sustainable development.

CN119327465APending Publication Date: 2025-01-21HEFEI ZHONGAN QINGYUAN ENVIRONMENTAL PROTECTION TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411309284.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

In the prior art, Co2+ is prone to secondary pollution in a homogeneous catalytic system and lacks significant synergistic performance, making it difficult to effectively remove trace amounts of difficult-to-degrade organic pollutants in water bodies.

Method used

By packing ZIF-67 in the ZIF-8 material, a series of treatment is performed to form a Z-67/8@c/n catalyst. Interception of macromolecular impurities.

Benefits of technology

The efficient ROS generation ability has been achieved, which significantly shortens the migration distance of ROS to pollutants, improves the degradation efficiency of pollutants, and does not cause secondary pollution, which is in line with the principle of sustainable development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119327465A_ABST
    Figure CN119327465A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a Z-67 / 8-coated C / N catalyst for persulfate advanced oxidation. The preparation method comprises the following steps: S1, carrying out mixed reaction on a cobalt nitrate hexahydrate solution and a di-methylimidazole solution, and carrying out aging, alcohol washing and vacuum drying to prepare ZIF-67; s2, performing in-situ growth of ZIF-8 on the surface of the ZIF-67 by using zinc nitrate hexahydrate and di-methylimidazole, and performing aging, alcohol washing and vacuum drying to obtain a Zn / Co-ZIF precursor; and S3, carrying out high-temperature calcination on the Zn / Co-ZIF precursor in an N2 atmosphere to obtain a solid, namely the Z-67 / 8-coated C / N catalyst. The invention also provides the Z-67 / 8-coated C / N catalyst prepared by the method and application of the catalyst in wastewater treatment. The method has the advantages that the raw materials are easy to obtain, the preparation process is simple, the prepared catalyst is good in catalytic effect and low in loss rate, and secondary pollution cannot be caused in the catalytic process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of water treatment, and in particular to a Z-67 / 8@C / N catalyst for persulfate advanced oxidation, and a preparation method and application thereof. Background Art

[0002] In recent decades, due to the excessive discharge of pollutants such as chemicals, pharmaceuticals, and endocrine disruptors, trace amounts of recalcitrant organic matter in water bodies have become a serious threat to the ecological environment, human health, and sustainable social development. Efficient treatment methods are urgently needed to remove these trace recalcitrant organic pollutants from water bodies.

[0003] Among the current methods, the persulfate-based advanced oxidation technology (SR-AOP) has been widely studied and applied to the treatment of trace refractory organic pollutants in water bodies due to its high oxidation potential and selectivity. It includes peroxymonosulfate (PMS) reaction and peroxydisulfate (PDS) reaction. Among them, PMS, as a good precursor for the production of various free radicals and non-free radicals, shows superior performance than PDS in terms of activation mode and pollutant degradation rate. Advanced oxidation technology based on PMS has been considered to be an effective means to deal with organic pollutants. Previous studies have confirmed that Co species is thermodynamically more susceptible to HSO5 - Therefore, cobalt-based heterogeneous catalysts are the best candidates for activating PMS to generate reactive oxygen species (ROS). However, for homogeneous catalytic systems, Co 2+ Due to its easy leaching and aggregation characteristics, it is very easy to cause secondary pollution during the catalytic process. Therefore, it is urgent to design new Co-based catalysts with sufficient activity and overcome its metal leaching pollution problem.

[0004] Metal-organic frameworks (MOFs) are porous inorganic-organic hybrid metal-oxygen clusters linked by organic ligands. Their organic ligand structure and π-π conjugated interactions with aromatic organic compounds can significantly improve the efficiency of ROS utilization. In recent years, catalysts based on a Co-centered, zeolitic imidazole framework MOF (ZIF-67) with a sodalite topology have been extensively studied in SR-AOPs. They offer the significant advantage of activating PMS, thereby significantly improving reaction efficiency. However, a ZIF-derived reaction system with significant synergistic properties has yet to be established. Inspired by this, the present invention encapsulates ZIF-67 within a Zn-centered, sodalite topological MOF (ZIF-8) and employs a series of methods to create a yolk-shell ZIF derivative. This ZIF-derived catalyst, endowed with efficient ROS generation, significantly shortens the migration distance of ROS to pollutants. Nanoscale spatial confinement can significantly accelerate pollutant degradation. More importantly, after derivatization treatment, the MOF shell can form a porous structure, which provides a possible pathway for the interception of large molecular impurities and the passage of small molecules of non-degradable organic pollutants, which is of great significance for the selective removal of pollutants in complex water bodies. Summary of the Invention

[0005] The technical problem to be solved by the present invention is to provide a Z-67 / 8@C / N catalyst for advanced persulfate oxidation and its preparation method and application. The catalyst has good catalytic effect, low loss rate, and the catalytic process does not cause secondary pollution.

[0006] The present invention adopts the following technical solutions to solve the above technical problems:

[0007] A method for preparing a Z-67 / 8@C / N catalyst for persulfate advanced oxidation comprises the following steps:

[0008] S1, using a cobalt nitrate hexahydrate solution and a dimethylimidazole solution to react, aging, alcohol washing and vacuum drying to prepare ZIF-67;

[0009] S2, using zinc nitrate hexahydrate and dimethylimidazole to in situ grow ZIF-8 on the prepared ZIF-67 surface, and then aging, alcohol washing and vacuum drying to obtain Zn / Co-ZIF precursor;

[0010] S3. The Zn / Co-ZIF precursor is calcined at high temperature in a N2 atmosphere, and the resulting solid is the desired Z-67 / 8@C / N catalyst.

[0011] As one of the preferred embodiments of the present invention, in step S1, the cobalt nitrate hexahydrate solution is prepared by adding cobalt nitrate hexahydrate solid into methanol and dissolving it by ultrasonication.

[0012] More preferably, 1.4 g of solid cobalt nitrate hexahydrate is added to 60 mL of methanol and dissolved by ultrasonication.

[0013] As one of the preferred embodiments of the present invention, in step S1, the dimethylimidazole solution is prepared by adding dimethylimidazole solid into methanol and dissolving it by ultrasonication.

[0014] More preferably, 2.43 g of dimethylimidazole solid is added to 60 mL of methanol and dissolved by ultrasonication.

[0015] As one of the preferred embodiments of the present invention, in step S1, the mixing reaction method is: titrating the dimethylimidazole solution into the cobalt nitrate hexahydrate solution, stirring and aging.

[0016] More preferably, the dimethylimidazole solution is titrated into the cobalt nitrate hexahydrate solution, stirred and aged at 25°C.

[0017] As one of the preferred embodiments of the present invention, in step S2, the in situ growth method is: ultrasonically dispersing the obtained ZIF-67 solid in methanol, continuously stirring and adding zinc nitrate hexahydrate to the dispersion, then adding dimethylimidazole to the dispersion, stirring and dissolving, and then transferring the solution to a hydrothermal reactor for hydrothermal reaction.

[0018] More preferably, 0.2 g of the obtained ZIF-67 solid is ultrasonically dispersed in 120 mL of methanol, stirred continuously, and 2.936 g of zinc nitrate hexahydrate is added to the dispersion, followed by adding 2.43 g of dimethylimidazole to the dispersion. After stirring and dissolving, the solution is transferred to a hydrothermal reactor for hydrothermal reaction.

[0019] As one of the preferred embodiments of the present invention, the reaction temperature of the hydrothermal reaction is 100° C. and the reaction time is 12 h.

[0020] As one of the preferred embodiments of the present invention, in step S1 and step S2, the aging temperature is 25° C. and the aging time is 24 h.

[0021] As one of the preferred embodiments of the present invention, in step S1 and step S2, the alcohol washing method is: collecting the aged precipitate by centrifugation, fully dispersing it in a methanol solution, and obtaining the precipitate by centrifugation, and repeating this process three times.

[0022] As one of the preferred embodiments of the present invention, in step S1 and step S2, the vacuum drying temperature is 60° C., and the vacuum drying time is 24 h.

[0023] As one of the preferred embodiments of the present invention, in step S3, the high-temperature calcination method in N2 atmosphere is as follows: the Zn / Co-ZIF precursor precipitate obtained by vacuum drying is placed in a tube furnace, and N2 is introduced, and the temperature is raised to 800°C at a rate of 5°C / min and maintained for 3 hours, and then taken out after cooling to room temperature.

[0024] As one of the preferred embodiments of the present invention, in step S3, the product of high-temperature calcination in a N2 atmosphere is placed in a container for dry storage, thereby preparing the Z-67 / 8@C / N catalyst.

[0025] A Z-67 / 8@C / N catalyst for persulfate advanced oxidation is prepared by any of the above methods.

[0026] An application of the Z-67 / 8@C / N catalyst for persulfate advanced oxidation in wastewater treatment.

[0027] The advantages of the present invention over the prior art are:

[0028] (1) The catalyst of the present invention has a significant catalytic effect, and its catalytic ability is stronger than that of common iron-carbon catalysts on the market, and its catalytic stability is good. At the same time, based on the analysis of the results of the pollutant degradation cycle experiment, the catalytic process of the catalyst of the present invention will not cause secondary pollution, which is in line with the principle of sustainable development.

[0029] (2) The raw materials of the catalyst of the present invention are all common chemical materials, cheap and easily available, and non-toxic;

[0030] (3) The catalyst preparation process of the present invention is simple and the production cost is low;

[0031] (4) The catalyst solid prepared by the present invention is magnetic, easy to recycle, has a low metal dissolution rate, is easy to add directly to sewage, and can be used as a long-term catalyst for advanced oxidation reactors. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a comparison of the SMX concentration changes under catalytic degradation of the Z-67 / 8@C / N high-efficiency catalyst, the Z-67@C catalyst, and the Z-8@C catalyst in Experimental Example 1;

[0033] Figure 2 This is a comparison chart of the concentration changes of SMX catalytically degraded by the Z-67 / 8@C / N high-efficiency catalyst in experimental example 2 under water sample conditions with different initial pH values;

[0034] Figure 3 This is a comparison chart of the concentration changes of SMX catalytically degraded by the Z-67 / 8@C / N high-efficiency catalyst in Experimental Example 3 under different catalyst dosage conditions;

[0035] Figure 4 This is a comparison chart of the concentration changes of SMX catalytically degraded by the Z-67 / 8@C / N high-efficiency catalyst in Experimental Example 3 under the conditions of different oxidant KHSO5 dosages;

[0036] Figure 5 This is a comparison chart of the removal rates of SMX by the Z-67 / 8@C / N high-efficiency catalyst under different SMX concentrations in Experimental Example 3;

[0037] Figure 6 This is a comparison chart of the removal rates of SMX by the Z-67 / 8@C / N high-efficiency catalyst in Experimental Example 3 when different quenchers are added to the pollutant system.

[0038] Figure 7 This is a comparison chart of the removal rate of SMX catalytically degraded by the Z-67 / 8@C / N high-efficiency catalyst after five cycle experiments and heat treatment in Experimental Example 5. DETAILED DESCRIPTION

[0039] The following examples of the present invention are described in detail. These examples are implemented based on the technical solutions of the present invention, and detailed implementation methods and specific operating procedures are provided. However, the scope of protection of the present invention is not limited to the following examples. At the same time, the reagents, experimental equipment and experimental methods used in the following examples are conventional reagents, equipment and methods in the art unless otherwise specified, and are not described in detail.

[0040] Example 1

[0041] The preparation method of the Z-67 / 8@C / N high-efficiency catalyst of this embodiment is as follows:

[0042] S1. Synthesis of ZIF-67:

[0043] ① Add 1.4 g of Co(NO3)2·6H2O to 60 mL of methanol and dissolve it by ultrasonication to prepare a 23.3 g / L cobalt nitrate hexahydrate solution.

[0044] ② Add 2.43 g of dimethylimidazole (2-Melm) to 60 mL of methanol and dissolve it by ultrasonication to prepare a 40.5 g / L dimethylimidazole solution.

[0045] ③ Titrate the prepared dimethylimidazole solution into the cobalt nitrate hexahydrate solution (1:1 by volume), stir and mix at 25°C and age for 24 hours.

[0046] ④ After aging, the mixture was washed three times with methanol (the precipitate after aging was collected by centrifugation, fully dispersed in methanol solution, and centrifuged to obtain the precipitate, and repeated three times), and vacuum dried at a drying temperature of 60°C for 24 h to obtain ZIF-67 crystals.

[0047] S2. Synthesis of Zn / Co-ZIF precursor:

[0048] ① Take 0.2g of ZIF-67 crystals prepared in the above steps and ultrasonically disperse them in 120mL of methanol. Stir continuously and add 2.936g of Zn(NO3)2·6H2O to the dispersion. Then add 2.43g of dimethylimidazole (2-Melm) to the dispersion. After stirring and dissolving, put it into a reactor and heat it to 100℃ for hydrothermal reaction. The reaction temperature is 100℃ and the reaction time is 12h.

[0049] ② The resulting mixture was washed three times with methanol (the precipitate was collected by centrifugation, fully dispersed in a methanol solution, and the precipitate was obtained by centrifugation, and repeated three times), and vacuum dried at a drying temperature of 60°C for 24 h to obtain a Zn / Co-ZIF precursor.

[0050] S3, post-processing:

[0051] The Zn / Co-ZIF precursor obtained by vacuum drying was placed in a tube furnace and N2 was introduced. The temperature was raised to 800℃ at a rate of 5℃ / min and maintained for 3h. After cooling to room temperature, it was taken out and placed in a container for dry storage to obtain the target Z-67 / 8@C / N catalyst high efficiency agent powder.

[0052] Comparative Example 1

[0053] A Z-67@C catalyst in this comparative example uses ZIF-67 as a precursor and is prepared as follows:

[0054] S1. Synthesis of ZIF-67:

[0055] Same as Example 1.

[0056] S2. Post-processing:

[0057] The ZIF-67 obtained in S1 was placed in a tube furnace and nitrogen was introduced. The temperature was raised to 800°C at a rate of 5°C / min and maintained for 3 h. After cooling to room temperature, the ZIF-67 was taken out and placed in a container for drying to obtain Z-67@C catalyst powder.

[0058] Comparative Example 2

[0059] A Z-8@C catalyst in this comparative example uses ZIF-8 as a precursor and is prepared as follows:

[0060] S1. Synthesis of ZIF-8:

[0061] ① Add 2.936 g of Zn(NO3)2·6H2O to 60 mL of methanol and dissolve it by ultrasonication to prepare a 48.9 g / L zinc nitrate hexahydrate solution.

[0062] ② Add 2.43 g of dimethylimidazole (2-Melm) to 60 mL of methanol and dissolve it by ultrasonication to prepare a 40.5 g / L dimethylimidazole solution.

[0063] ③ Titrate the prepared dimethylimidazole solution into zinc nitrate hexahydrate solution (1:1 by volume), stir and mix at 25°C and age for 24 hours.

[0064] ④ After aging, the mixture was washed three times with methanol (the precipitate after aging was collected by centrifugation, fully dispersed in methanol solution, and the precipitate was obtained by centrifugation, and repeated three times), and vacuum dried at a drying temperature of 60°C for 24 h to obtain ZIF-8 crystals.

[0065] S2. Post-processing:

[0066] The ZIF-8 crystal was placed in a tube furnace and nitrogen was introduced. The temperature was raised to 800°C at a rate of 5°C / min and maintained for 3 hours. After cooling to room temperature, the crystal was taken out and placed in a container for drying to obtain Z-8@C catalyst powder.

[0067] With reference to the conclusions drawn from the watershed survey, in the following experimental examples, sulfamethoxazole (SMX), a representative trace refractory organic pollutant, was selected as the target pollutant, and potassium persulfate (KHSO5) was selected as the oxidant to evaluate the catalytic performance of the Z-67 / 8@C / N catalyst of the present invention.

[0068] Experimental Example 1

[0069] This experimental example is used to compare and explore the removal effects of Z-67 / 8@C / N catalyst, Z-67@C catalyst, and Z-8@C catalyst on sulfamethoxazole (SMX).

[0070] Prepare a 30 mg / L SMX solution using SMX solution and deionized water, then add 0.03 g of catalyst and 3 mM (0.0531 g) KHSO5 to the solution. Mix on an orbital shaker to allow the reaction to complete. Remove 1 mL of the reaction solution at predetermined intervals, filter through a 0.22 μm filter membrane, and use MeOH to quench unreacted SO4. ·- and ·OH, and were detected by high-performance liquid chromatography. The pH value was controlled by NaOH and H2SO4. Each experiment was repeated three times.

[0071] The catalytic degradation removal rates of SMX by Z-67 / 8@C / N high-efficiency catalyst (prepared in Example 1), Z-67@C catalyst (prepared in Comparative Example 1), and Z-8@C catalyst (prepared in Comparative Example 2) are shown in Tables 1, 2, and 3 below. Figure 1 Comparison of SMX concentration changes under catalytic degradation of three catalysts.

[0072] As shown in Tables 1, 2, and 3, both the Z-67 / 8@C / N high-efficiency catalyst and the Z-67@C catalyst have very significant catalytic degradation effects on SMX. They can catalytically degrade more than 90% of the pollutants in the water sample within 15 minutes, and more than 96% of the pollutants in the water sample after 60 minutes, and can catalyze the degradation to the reaction endpoint. The catalytic degradation ability of the Z-8@C catalyst is slightly weaker, and it can catalytically degrade 70% of the pollutants in the water body in 60 minutes. Analysis shows that the reason may be that high-temperature calcination causes a large amount of Zn species to volatilize, reducing the catalytic active sites and reducing the catalytic performance.

[0073] Depend on Figure 1 By comparison, it can be seen that the pollutant concentration dropped most significantly within the initial 5 minutes, indicating that all three catalysts had relatively significant catalytic degradation capabilities in the initial stage; the catalytic degradation behavior of Z-67@C basically stopped after 15 minutes. Analysis showed that the Co species of Z-67@C existed in the form of nano-zero-valent cobalt after high-temperature calcination. This substance has very significant short-term catalytic ability, but is easy to dissolve, has a high loss rate, and has poor long-term catalytic performance; Z-67 / 8@C / N has a relatively slow catalytic degradation rate and can ultimately degrade 98% of the pollutants in the water sample. It is the one with the strongest degradation ability among the above three catalysts and has good long-term catalytic ability.

[0074] The above description shows that, compared with other similar catalysts, the Z-67 / 8@C / N high-efficiency catalyst of the present invention has significant advantages in catalytic degradation of pollutants.

[0075] Table 1 Catalytic degradation removal rate of SMX by Z-67 / 8@C / N high efficiency catalyst

[0076]

[0077] Table 2 Catalytic degradation removal rate of SMX by Z-67@C catalyst

[0078]

[0079] Table 3 Catalytic degradation removal rate of SMX by Z-8@C catalyst

[0080]

[0081] Experimental Example 2

[0082] This experimental example is used to explore the catalytic degradation effect of the Z-67 / 8@C / N high-efficiency catalyst of the present invention on sulfamethoxazole (SMX) in water samples with different pH values.

[0083] A 30 mg / L SMX solution was prepared using SMX solution and deionized water. The pH value of the raw water sample was measured to be 7.53. NaOH and H2SO4 were used to adjust the pH values ​​of the water samples to 3, 5, 7, 9, and 11 as control groups. 0.03 g of catalyst and 3 mM (0.0531 g) KHSO5 were added to the above solutions. The mixture was mixed on an orbital shaker to allow for sufficient reaction. 1 mL of the reaction solution was removed at predetermined time intervals, filtered through a 0.22 μm filter membrane, and unreacted SO4 was quenched with MeOH. ·- and ·OH, and were detected by high performance liquid chromatography. Each experiment was repeated three times.

[0084] Table 4 Catalytic degradation removal rate of SMX solution Z-67 / 8@C / N high efficiency catalyst at pH=3

[0085]

[0086] Table 5 Catalytic degradation removal rate of SMX solution Z-67 / 8@C / N high efficiency catalyst at pH=5

[0087]

[0088] Table 6 Catalytic degradation removal rate of SMX solution Z-67 / 8@C / N high efficiency catalyst at pH=7

[0089]

[0090] Table 7 Catalytic degradation removal rate of SMX solution Z-67 / 8@C / N high-efficiency catalyst at pH = 7.53 (raw water pH)

[0091]

[0092] Table 8 Catalytic degradation removal rate of SMX solution Z-67 / 8@C / N high efficiency catalyst at pH=9

[0093]

[0094] Table 9 Catalytic degradation removal rate of SMX solution Z-67 / 8@C / N high efficiency catalyst at pH=11

[0095]

[0096] The catalytic degradation removal rates of SMX by Z-67 / 8@C / N high-efficiency catalyst under the conditions of initial water sample pH of 3, 5, 7, 7.53 (raw water pH), 9, and 11 are shown in Tables 4, 5, 6, 7, 8, and 9 below. Figure 2 Comparison of the concentration changes of SMX catalytically degraded by Z-67 / 8@C / N high-efficiency catalyst under water sample conditions with different initial pH values.

[0097] From Tables 4 to 9 and Figure 2 It can be seen that: under different raw water pH conditions, the Z-67 / 8@C / N high-efficiency catalyst can play a significant catalytic degradation role, and can degrade more than 90% of SMX in the water sample after 60 minutes. Among them, the water sample pH of 3 shows an inhibitory effect on the catalyst, and 89.85% of SMX can be degraded in 60 minutes; when the water sample pH = 11, the catalyst can degrade 98% of SMX within 5 minutes. The concentration change trends of SMX are similar when the water sample pH is 5, 7, 7.53, and 9.

[0098] The above shows that the Z-67 / 8@C / N high-efficiency catalyst of the present invention has good pH adaptability for the catalytic degradation of pollutants. It can play a good catalytic degradation role in sewage with a pH range of 3 to 11, and exhibits better catalytic performance in neutral to alkaline environments. It is suitable for advanced oxidation catalysis in water bodies with most pH values.

[0099] Experimental Example 3

[0100] This experimental example is used to explore the catalytic degradation performance of Z-67 / 8@C / N high-efficiency catalyst under different catalyst dosages, oxidant dosages, and pollutant concentrations.

[0101] 1. Catalytic degradation performance of Z-67 / 8@C / N high-efficiency catalyst under different catalyst dosages.

[0102] Prepare 30mg / L SMX solution with SMX solution and deionized water. The catalyst dosage is selected as 0.01g, 0.02g, 0.03g, 0.04g, and 0.05g respectively. The KHSO5 dosage is 3mM (0.0531g) and added to the above pollutant solution. Mix on an orbital shaker to allow the reaction to complete. At predetermined time intervals, remove 1mL of the reaction solution, filter through a 0.22μm filter membrane, and use MeOH to quench the unreacted SO4 ·- and ·OH, and were detected by high performance liquid chromatography. Each experiment was repeated three times.

[0103] Table 10 Catalytic degradation removal rate of SMX reaction system with a catalyst dosage of 0.01g in Z-67 / 8@C / N

[0104]

[0105] Table 11 Catalytic degradation removal rate of SMX reaction system with a Z-67 / 8@C / N catalyst dosage of 0.02g

[0106]

[0107]

[0108] Table 12 Catalytic degradation removal rate of SMX reaction system with a Z-67 / 8@C / N catalyst dosage of 0.03g

[0109]

[0110] Table 13 Catalytic degradation removal rate of SMX reaction system with a Z-67 / 8@C / N catalyst dosage of 0.04g

[0111]

[0112] Table 14 Catalytic degradation removal rate of SMX reaction system with a catalyst dosage of 0.05g of Z-67 / 8@C / N

[0113]

[0114] The catalytic degradation removal rates of the SMX reaction system with Z-67 / 8@C / N high-efficiency catalyst dosages of 0.01g, 0.02g, 0.03g, 0.04g, and 0.05g are shown in Tables 10 to 14. Figure 3 The figure shows the comparison of the concentration changes of SMX during catalytic degradation under different dosages of Z-67 / 8@C / N high-efficiency catalyst.

[0115] From Tables 10 to 14 and Figure 3 The results show that the pollutant removal rate gradually increases with increasing catalyst dosage. At a catalyst dosage of 0.01 g, only 81.43% of the SMX in the water sample was degraded in 60 minutes. However, when the catalyst dosage was increased to 0.02 g, 92.96% of the SMX was degraded in 60 minutes. The degradation endpoint remained largely unchanged with further increases in catalyst dosage. Considering both manufacturing cost and catalytic efficiency, 0.03 g of catalyst dosage was found to be the optimal catalyst dosage.

[0116] 2. Catalytic degradation performance of Z-67 / 8@C / N high-efficiency catalyst under different oxidant dosage conditions.

[0117] A 30 mg / L SMX solution was prepared using SMX solution and deionized water. The oxidant KHSO5 was added in amounts of 1 mM (0.0177 g), 2 mM (0.0354 g), 3 mM (0.0531 g), 4 mM (0.0708 g), and 5 mM (0.0885 g), respectively. The catalyst was added in an amount of 0.03 g and added to the above pollutant solution. The mixture was mixed on an orbital shaker to allow the reaction to proceed fully. 1 mL of the reaction solution was removed at predetermined time intervals, filtered through a 0.22 μm filter membrane, and MeOH was used to quench the unreacted SO4. ·- and ·OH, and were detected by high performance liquid chromatography. Each experiment was repeated three times.

[0118] Table 15 Catalytic degradation removal rate of SMX reaction system with KHSO5 dosage of 1mM

[0119]

[0120] Table 16 Catalytic degradation removal rate of SMX reaction system with KHSO5 dosage of 2mM

[0121]

[0122]

[0123] Table 17 Catalytic degradation removal rate of SMX reaction system with KHSO5 dosage of 3mM

[0124]

[0125] Table 18 Catalytic degradation removal rate of SMX reaction system with KHSO5 dosage of 4mM

[0126]

[0127] Table 19 Catalytic degradation removal rate of SMX reaction system with KHSO5 dosage of 5mM

[0128]

[0129] The catalytic degradation removal rates of the SMX reaction systems with the oxidant KHSO5 dosages of 1mM (0.0177g), 2mM (0.0354g), 3mM (0.0531g), 4mM (0.0708g), and 5mM (0.0885g) are shown in Tables 15 to 19. Figure 4 This is a comparison of the concentration changes of SMX catalytically degraded by Z-67 / 8@C / N high-efficiency catalyst under different oxidant KHSO5 dosage conditions.

[0130] From Tables 15 to 19 and Figure 4 The results show that the catalytic reaction rate increases with increasing oxidant dosage. At a 2mM oxidant dosage, 93.80% of the SMX in the water sample was degraded in 60 minutes. At 3mM, 97.88% of the SMX in the water sample was degraded in 60 minutes. Further increases in oxidant dosage did not significantly increase the pollutant removal rate, nor did the degradation endpoint change significantly. Considering both manufacturing cost and catalytic efficiency, 3mM oxidant catalyst dosage was found to be the optimal dosage.

[0131] 3. Catalytic degradation performance of Z-67 / 8@C / N high-efficiency catalyst under different pollutant concentration conditions.

[0132] Different volumes of SMX solution (100 mg / L) were added to deionized water to prepare pollutant solutions with concentrations of 10 mg / L, 20 mg / L, 30 mg / L, 40 mg / L, and 50 mg / L. The oxidant KHSO5 was added at a dosage of 3 mM (0.0531 g) and the Z-67 / 8@C / N high-efficiency catalyst was added at a dosage of 0.03 g. The mixture was mixed on an orbital shaker to ensure sufficient reaction. 1 mL of the reaction solution was removed at predetermined time intervals, filtered through a 0.22 μm filter membrane, and unreacted SO4 was quenched with MeOH. ·- and ·OH, and were detected by high performance liquid chromatography. Each experiment was repeated three times.

[0133] Table 20 Catalytic degradation removal rate of the reaction system with SMX concentration of 10 mg / L

[0134]

[0135] Table 21 Catalytic degradation removal rate of the reaction system with SMX concentration of 20 mg / L

[0136]

[0137]

[0138] Table 22 Catalytic degradation removal rate of the reaction system with SMX concentration of 30 mg / L

[0139]

[0140] Table 23 Catalytic degradation removal rate of the reaction system with SMX concentration of 40 mg / L

[0141]

[0142] Table 24 Catalytic degradation removal rate of the reaction system with SMX concentration of 50 mg / L

[0143]

[0144]

[0145] The catalytic degradation removal rates of the SMX reaction system with SMX concentrations of 10 mg / L, 20 mg / L, 30 mg / L, 40 mg / L, and 50 mg / L are shown in Tables 20 to 24. Figure 5 The comparison of the removal rate of SMX by Z-67 / 8@C / N high-efficiency catalyst under different SMX concentrations.

[0146] From Tables 20 to 24 and Figure 5It can be seen that as the pollutant concentration gradually increases, the pollutant removal rate gradually decreases. When the SMX concentration is 10mg / L, 20mg / L, and 30mg / L, the catalytic degradation removal rate of the reaction system can reach more than 97%. When the SMX concentration continues to increase, the pollutant removal rate decreases to below 90%, indicating that 3mM (0.0531g) of the oxidant KHSO5 and 0.03g of the Z-67 / 8@C / N high-efficiency catalyst can effectively remove 30mg / L of SMX. Combined with the above, it can be concluded that the Z-67 / 8@C / N high-efficiency catalyst has good applicability for the catalytic degradation of pollutants. It can play a significant catalytic degradation role in wastewater SMX concentrations of 30mg / L and below, and is suitable for advanced oxidation catalysis in most natural water bodies and industrial wastewater.

[0147] Experimental Example 4

[0148] This experimental example is used to explore which ROS plays a decisive role in the catalytic degradation process of Z-67 / 8@C / N high-efficiency catalyst.

[0149] A 30 mg / L SMX solution was prepared using SMX solution and deionized water. Methanol (500 mM), tert-butyl alcohol (500 mM), furfuryl alcohol (500 mM), p-benzoquinone (10 mM), and silver nitrate (10 mM) were added to each solution to inhibit the effects of the corresponding ROS. 0.03 g of the catalyst and 3 mM (0.0531 g) of KHSO5 were then added to the above solution. The mixture was mixed on an orbital shaker to allow for sufficient reaction. 1 mL of the reaction solution was removed at predetermined time intervals, filtered through a 0.22 μm filter membrane, and unreacted SO4 was quenched using MeOH. ·- and ·OH, and were detected by high performance liquid chromatography. Each experiment was repeated three times.

[0150] Table 25 Catalytic degradation removal rate of the reaction system with 500 mM methanol added

[0151]

[0152] Table 26 Catalytic degradation removal rate of the reaction system with 500 mM tert-butyl alcohol added

[0153]

[0154] Table 27 Catalytic degradation removal rate of the reaction system with 500mM furfuryl alcohol added

[0155]

[0156] Table 28 Catalytic degradation removal rate of the reaction system with 10 mM p-benzoquinone

[0157]

[0158]

[0159] Table 29 Catalytic degradation removal rate of the reaction system with 10 mM silver nitrate added

[0160]

[0161] The catalytic degradation removal rates of the SMX reaction systems in which methanol (500 mM), tert-butanol (500 mM), furfuryl alcohol (500 mM), p-benzoquinone (10 mM), and silver nitrate (10 mM) were added to the SMX solutions are shown in Tables 25 to 29. Figure 6 To compare the removal rates of SMX by the Z-67 / 8@C / N high-efficiency catalyst under the conditions of adding different quenchers to the pollutant system.

[0162] From Tables 25 to 29 and Figure 6 It can be seen that: tert-butanol has no inhibitory effect on the catalytic degradation of pollutants, indicating that hydroxyl radicals are not produced in this catalytic reaction system; methanol has a weak inhibitory effect on the catalytic degradation of pollutants, indicating that sulfate radicals play a certain role in this catalytic reaction system, but their contribution is very small; benzoquinone and silver nitrate have a strong but unstable inhibitory effect on the catalytic degradation of pollutants, indicating that superoxide radicals may jointly dominate the catalytic degradation of this reaction system with singlet oxygen; furfuryl alcohol has a significant inhibitory effect on the catalytic degradation of pollutants, which can be analyzed as a non-free radical-dominated catalytic degradation system, and the dominant ROS is singlet oxygen 1 O2. As a ROS with wide catalytic oxidation applicability, 1 O2 can be applied to most sewage systems, including natural water bodies and industrial wastewater, with high reaction rate and good degradation effect. This catalyst is suitable for advanced oxidation catalysis in most natural water bodies and industrial wastewater.

[0163] Experimental Example 5

[0164] This experimental example is used to explore the catalytic degradation effect of the Z-67 / 8@C / N high-efficiency catalyst of the present invention on sulfamethoxazole (SMX) in multiple cycles to evaluate its stability and environmental friendliness during the catalytic process.

[0165] Prepare a 30 mg / L SMX solution using SMX solution and deionized water. Add 0.03 g of catalyst and 3 mM (0.0531 g) KHSO5 to the solution. Mix on an orbital shaker to allow the reaction to complete. Remove 1 mL of the reaction solution at predetermined intervals, filter through a 0.22 μm filter membrane, and use MeOH to quench unreacted SO4. ·-and ·OH, and tested by HPLC. After one degradation cycle, the catalyst was collected and dried, then placed in the next set of pollutant solutions with the same composition. The catalytic degradation was repeated five times, and the degradation results were compared by HPLC. After the fifth cycle, the catalyst sample was heat-treated (300°C) and then placed in the same pollutant solution to test its catalytic degradation.

[0166] Figure 7 Comparison of the removal rate of SMX catalytically degraded by Z-67 / 8@C / N high-efficiency catalyst after five cycle experiments and heat treatment.

[0167] The highly efficient Z-67 / 8@C / N catalyst achieved removal rates of 97.2%, 96.9%, 91.9%, 88.1%, and 85.8% in the first, second, third, fourth, and fifth cycles, respectively. The SMX removal rate gradually decreased over the five runs, but a high pollutant removal rate was still maintained. After the fifth cycle, the Z-67 / 8@C / N sample was subjected to a further heat treatment (300°C), and its catalytic degradation rate for SMX was restored to 96.1%. This indicates that the decrease in SMX removal rate over multiple cycles is due to adsorption of pollutants on the catalyst surface, rather than catalyst passivation.

[0168] The above demonstrates that the Z-67 / 8@C / N high-efficiency catalyst of the present invention exhibits good stability in catalytic degradation of pollutants, performing effectively in multiple degradation cycles. Furthermore, after heat treatment of the re-used catalyst, its catalytic degradation rate can be restored to a high level. This demonstrates the catalyst's excellent environmental stability, effectively preventing metal leaching and preventing secondary pollution, thus complying with the principles of sustainable development.

[0169] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a Z-67 / 8@C / N catalyst for persulfate advanced oxidation, characterized in that: The steps include: S1, preparing ZIF-67 by mixing a cobalt nitrate hexahydrate solution and a dimethylimidazole solution, aging, washing with alcohol and vacuum drying; S2, using zinc nitrate hexahydrate and dimethylimidazole to in situ grow ZIF-8 on the surface of the prepared ZIF-67, and obtaining a Zn / Co-ZIF precursor after aging, alcohol washing and vacuum drying; S3. The Zn / Co-ZIF precursor is calcined at high temperature in a N2 atmosphere, and the resulting solid is the desired Z-67 / 8@C / N catalyst.

2. The method for preparing the Z-67 / 8@C / N catalyst for persulfate advanced oxidation according to claim 1, characterized in that: In the step S1, the preparation method of the cobalt nitrate hexahydrate solution and the dimethylimidazole solution is: adding the corresponding cobalt nitrate hexahydrate solid or dimethylimidazole solid into methanol, and dissolving by ultrasonication to obtain the solution.

3. The method for preparing the Z-67 / 8@C / N catalyst for persulfate advanced oxidation according to claim 1, characterized in that: In step S1, the mixing reaction method is: titrating the dimethylimidazole solution into the cobalt nitrate hexahydrate solution, stirring and aging.

4. The method for preparing the Z-67 / 8@C / N catalyst for persulfate advanced oxidation according to claim 1, characterized in that: In step S2, the in-situ growth method is: ultrasonically dispersing the obtained ZIF-67 solid in methanol, continuously stirring and adding zinc nitrate hexahydrate to the dispersion, then adding dimethylimidazole to the dispersion, stirring and dissolving, and then transferring the solution to a hydrothermal reactor for hydrothermal reaction.

5. The method for preparing the Z-67 / 8@C / N catalyst for persulfate advanced oxidation according to claim 4, characterized in that: The reaction temperature of the hydrothermal reaction is 100° C. and the reaction time is 12 h.

6. The method for preparing the Z-67 / 8@C / N catalyst for persulfate advanced oxidation according to claim 1, characterized in that: In the step S1 and step S2, the aging temperature is 25° C. and the aging time is 24 hours.

7. The method for preparing the Z-67 / 8@C / N catalyst for persulfate advanced oxidation according to claim 1, characterized in that: In the step S1 and step S2, the vacuum drying temperature is 60° C. and the vacuum drying time is 24 hours.

8. The method for preparing the Z-67 / 8@C / N catalyst for persulfate advanced oxidation according to claim 1, characterized in that: In step S3, the high-temperature calcination method in N2 atmosphere is as follows: the Zn / Co-ZIF precursor precipitate obtained by vacuum drying is placed in a tube furnace, and N2 is introduced, and the temperature is increased to 800°C at a rate of 5°C / min and maintained for 3h, and then taken out after cooling to room temperature.

9. A Z-67 / 8@C / N catalyst for persulfate advanced oxidation, characterized in that: The method is prepared by any one of claims 1 to 8.

10. Use of the Z-67 / 8@C / N catalyst for persulfate advanced oxidation as claimed in claim 9 in wastewater treatment.

Citation Information

Patent Citations

  • Nitrogen-doped hollow carbon polyhedron-carbon@nanotube-based monatomic cobalt catalyst capable of efficiently activating persulfate and preparation method thereof

    CN112169822A

  • Preparation method of Co-Zn / C-N catalyst and application of Co-Zn / C-N catalyst in reaction for synthesis of methanol through hydrogenation of CO2

    CN112808291A